PERAN PODCAST SEBAGAI MEDIA INFORMASI DAN HIBURAN (Survey terhadap podcaster dan pendengar podcast di Tangerang Selatan) - Oktavanisya, Vianka Desta; Fikry, Yasser (Transpublika Publisher, 2024)
Podcast (play-on demand) is one of the media whose users and applicants are increasing nowadays, not only to enjoy the content, some of them use podcast to be podcasters. But with improvements in technology, podcast, which is audio-based media, being disrupted into audio-visual media. Podcast have several advantages that attract listeners, in terms of content nor for ease of access. So, this study aims to explain the impact and role of podcasts as a medium of information and entertainment. The research method is descriptive qualitative with a phenomenological approach. Data were obtained through in-depth interview with adolescent informants aged 21-23 years of age. This research was carried out at the informant’s place and through virtual. The summary of the research results shows that podcasts have a positive impact on personal and have a big role as a medium of information and entertainment because; 1) podcast can be an alternative media; 2) various content according to their respective interest; 3) ease of access; 4) easy-to-understand language; 5) podcast are creative and innovative media.